2020
DOI: 10.26782/jmcms.spl.9/2020.05.00022
|View full text |Cite
|
Sign up to set email alerts
|

Early Fault Detection in Bearing Using Time Domain Technique: Faulty Bearing Seeded on Inner Raceway and Ball

Abstract: One of the most important assets in an industry would be rotating machines. The reliability and availability are very crucial in order to support the accomplishment of an industry field. Major and even minor faults in rotating machines cause a decrease in both productivity and cost efficiency. Various methods have been studied by researcher and introduced in the industry for the detection of an early fault in rotating machines. Vibration signal analysis is one of a standout amongst other methods. This research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The graph can be skewed on one hand or the other. The value of skewness can be both positive and negative [1]. In terms of the skewness values that are depicted in Figure 11, it can be observed that the skewness patterns for the five bearing health states are overlapping, and there is not any useful information that can be gained from them.…”
Section: Feature Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…The graph can be skewed on one hand or the other. The value of skewness can be both positive and negative [1]. In terms of the skewness values that are depicted in Figure 11, it can be observed that the skewness patterns for the five bearing health states are overlapping, and there is not any useful information that can be gained from them.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Rotating machinesare important for different industries, such as oil and gas industries, construction, and power plant industries.A catastrophic failure of rotating machinery would have a huge effect on the manufacturing sector. As the malfunction progresses, the machine's energy consumption will increase, while its performance will decrease.Gradually, followed by a sudden failure, will not only decrease production volume but will also result in increased operating costs for the reconstruction, as well as wasting time for the employees as they wait.On a larger scale, continued use of a defective machine could result in physical injury to the person operating the machine, and in the worst-case scenario, death [1]. A rolling bearing part is a critical com-ponent in engineering machinery, and even minor damage can result in unexpected production halts or industrial accidents.Bearing faults can occur for various reasons, including heavy loads that are unstable and inadequate lubrication [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation